“We Are Monitoring”. A Characterisation of Social Relationships at Gated Communities Using the Documentary Interpretation Method - Słaboń, Andrzej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article presents the main principles method of documentary interpretation. From this theoretical perspective the social relationships at gated communities in Cracow are analysed. Interviews were conducted with security personnel about the living conditions at gated communities, the relationships between inhabitants, and their own working conditions.